2020
DOI: 10.1002/marc.202000602
|View full text |Cite
|
Sign up to set email alerts
|

Silicone‐Ionic Liquid Elastomer Composite with Keratin as Reinforcing Agent Utilized as Pressure Sensor

Abstract: Development of a flexible pressure sensor is crucial for the future improvement of the wearable electronic devices designed to detect dynamic human motion. In this study, a novel pressure sensor with remarkably improved force sensing characteristics is obtained through combined usage of polydimethylsiloxane (PDMS) and ionic liquid (IL). Keratin is dispersed homogeneously in the PDMS matrix to serve as a reinforcing filler. High conductivity IL is employed as sensitivity‐enhancing constituent in the elastomer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…ILs consist of organic cations and inorganic anions, or vice versa, and therefore possess much higher conductivity than silicone ( Lu et al, 2020 ). Our previous work on IL-modified PDMS elastomers such as 1-ethylpyridinium tetrafluoroborate ( Su et al, 2020 ) and 1-butyl-3-methylimidazolium hexafluoroantimonate ( Liu et al, 2019 ; Liu et al, 2020b ) showed that these materials displayed slightly higher σ * values than that of the pure elastomer, albeit their overall conductivity was still considered to be exceptionally low. It is therefore also possible that LMS-EIL can be used as an additive to modify PDMS elastomers despite its improved complex conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…ILs consist of organic cations and inorganic anions, or vice versa, and therefore possess much higher conductivity than silicone ( Lu et al, 2020 ). Our previous work on IL-modified PDMS elastomers such as 1-ethylpyridinium tetrafluoroborate ( Su et al, 2020 ) and 1-butyl-3-methylimidazolium hexafluoroantimonate ( Liu et al, 2019 ; Liu et al, 2020b ) showed that these materials displayed slightly higher σ * values than that of the pure elastomer, albeit their overall conductivity was still considered to be exceptionally low. It is therefore also possible that LMS-EIL can be used as an additive to modify PDMS elastomers despite its improved complex conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance–pressure curve is shown in Figure b in which the sensitivity could be divided into three regions. When the applied pressure was within the range of 0–1 kPa, the sensitivity was 0.345 kPa –1 , which was much higher than the most common hydrogel-based pressure sensor in the literature (Figure e). , As the pressure was within the ranges of 1–3 kPa and 3–5 kPa, the sensitivity reached to 0.182 and 0.024 kPa, respectively. Figure c indicates that the hydrogel pressure sensor exhibited high sensitivity, and it could respond to the changes of different pressures as being subjected to the repeated compressive loading and unloading procedure.…”
Section: Resultsmentioning
confidence: 82%
“…[7,8] In contrast to piezoelectric and piezoresistive electronic sensors, the liquid-solid structure of IFS exhibited a very low Young's modulus and biocompatibility with high sensitivity. Since then, many researchers have tried to use a variety of ionic matrices, including ionic liquids, [9][10][11] polyelectrolytes, [12][13][14][15] and ionic gels, [16][17][18] to develop IFS for tactile perception. IFS can successfully respond to a variety of external stimuli, such as, pressure, [19][20][21] strain, [22,23] torsion, [24] and tangential force.…”
Section: Introductionmentioning
confidence: 99%